2015
DOI: 10.1515/aiht-2015-66-2651
|View full text |Cite
|
Sign up to set email alerts
|

A suggestion for royal jelly specifications / Prijedlog globalnih standarda za matičnu mliječ

Abstract: This article proposes guidelines for quality standards of royal jelly. The proposals are based on two sets of data; the first from our study of the factors that may affect the royal jelly's chemical composition (protein and sugar supplementation of beehives) and the second on the analysis of a great number of samples from across Greece to establish natural variability of this product. We compared our findings with the adopted national limits, the proposals of the working group of the International Honey Commis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
(3 reference statements)
4
30
0
3
Order By: Relevance
“…The content of 10-HDA in RJ is reported to be 0.8%–6.5%; moreover, it is known as a unique component of RJ because it is not detected in any other natural raw material, even in other bee products [ 11 , 22 , 38 ]. To our surprise, anti-cancer effects of 10-HDA in leukemia and ascitic tumors were first reported in approximately 60 years ago [ 39 , 40 ].…”
Section: Anti-cancer Effects Of Royal Jelly and Its Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of 10-HDA in RJ is reported to be 0.8%–6.5%; moreover, it is known as a unique component of RJ because it is not detected in any other natural raw material, even in other bee products [ 11 , 22 , 38 ]. To our surprise, anti-cancer effects of 10-HDA in leukemia and ascitic tumors were first reported in approximately 60 years ago [ 39 , 40 ].…”
Section: Anti-cancer Effects Of Royal Jelly and Its Componentsmentioning
confidence: 99%
“…Similarly, the biological roles and composition of various fractions of RJ are affected by such factors. Indeed, RJ composition varies by countries; for examples, the percentage of 10-HDA content in Brazil tended to be higher than that in other countries, including Japan, India, Turkey and Switzerland [ 38 ]. Furthermore, although it was reported that RJ (0.5–1 mg/mL) enhanced MCF-7 cell proliferation owing to the estrogenic activities of RJ via interaction with estrogen receptor [ 86 ], other investigators did not find similar pro-carcinogenic and estrogen-like activities by RJ supplied by other manufacturers [ 25 ].…”
Section: Limitations Of Studies On Biological Activities Of Royal mentioning
confidence: 99%
“…10 Các sản phẩm chứa sữa ong chúa hiện nay như sữa ong chúa tươi, sữa ong chúa đông khô, mật ong sữa chúa ... thường ít ghi nhãn về hàm lượng 10-HDA mà chỉ ghi tỷ lệ thành phần sữa ong chúa. Một số quốc gia như Thụy sỹ, Thổ Nhĩ Kỳ, Nhật Bản, Hàn Quốc, Ấn độ, Trung Quốc đã có quy định về hàm lượng tối thiểu của 10-HDA trong sữa ong chúa tươi là 1,4% [3], với Brazil giá trị quy định này trong sữa ong chúa tươi là 2,0%, và trong sữa ong chúa đông khô là 5,0% [4], Thái Lan và Thổ Nhĩ Kỳ có quy định đối với các sản phẩm khác chứa sữa ong chúa với hàm lượng 10-HAD tối thiểu là 0,16% [5]. Việc xác định hàm lượng thành phần này trong sữa ong chúa được thực hiện tại các phòng thí nghiệm bằng phương pháp sắc kí lỏng hiệu năng cao (HPLC) hoặc phương pháp sắc kí khí (GC).…”
Section: Giới Thiệuunclassified
“…It is produced by worker bees as a source of nutrition for larvae less than three days old and queen bees throughout their lives, it contains complex combinations of pheromones which control the honey bee colony hierarchy 101 . Royal jelly is a complex mixture of proteins, carbohydrates, fatty acids, sugars, lipids and vitamins 102 . Like honey, it contains several known antimicrobial compounds and several studies have shown that royal jelly, and its extracts have antimicrobial activity against a wide range of bacterial and fungal sp.…”
Section: Antimicrobial Properties Of Royal Jellymentioning
confidence: 99%
“…The extraction process has not only a high level of waste, with one group reporting the production of 180 mg from an initial 30 g sample of royal jelly 103 , but the exact extraction method chosen dictates which compounds will be obtained. Recently there has been an effort to standardise the extraction process and classify royal jelly 102,108 and work has been carried out to show the effect, if any, that processing may have on the activity of royal jelly. A recent study has shown that lyophilisation, which allows storage and further processing of the royal jelly, did not alter its antimicrobial activity against S. aureus, S. epidermidis, S. pneumoniae, E.coli, K. pneumoniae, Proteus mirabilis, S.…”
Section: Antimicrobial Properties Of Royal Jellymentioning
confidence: 99%